Action plan: Low carbon regional ports - Jens Froese; Malte Jahn; Jan Wedemeier; Matthäus Wuczkowski (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2019)
This action plan at hand will address the questions how ports can increase their efficiency, enhance their role in the industry, and become more sustainable. After presenting low carbon port activities within the DUAL ports project, the paper will derive implications for low carbon emission policies.
Keywords: 330